Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian Konsumen Mixue - Melan Rosmayanti (Journal on Education, 2023)
This study aims to determine and analyze the effect of brand image and brand awareness on purchasing decisions on Mixue. The population in this study were all mixue consumers. The sample in the study were 154 respondents obtained from distributing questionnaires by researchers. The method used in this research is a quantitative method. The instruments in this study were tested using validity and reliability tests which were complemented by the classic assumption test consisting of multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The data analysis technique uses multiple linear regression correlation coefficients consisting of the T test, F test, and the coefficient of determination test. Brand Image (X1), Brand Awareness (X2), and Purchase Decision (Y). The results of the multiple regression correlation coefficient yield the equation Y = -4.181 + 0.593 (X1) + 0.794 (X2) + e. The partial test results show that the brand image variable has a positive and significant effect on consumer purchasing decisions, and the brand awareness variable has a positive and significant effect on purchasing decisions. Simultaneous test results show that there is a positive and significant influence between brand image and brand awareness on Mixue consumer purchasing decisions.